The Effectiveness of the One-House-One-Alkurting Intervention in Improving Maternal Behavior to Detect the Risk of Stunting in Disadvantaged, Remote, and Outermost Areas - Demsa Simbolon; Lusi Andriani; Agustina Setia; Tobianus Hasasn; Nabila Putri; Monik Monik; Kelvin Setia Wati (Indonesian Journal of Global Health Research, 2024)
The problem of stunting in Indonesia is still high, with a prevalence between 17.6% and 42.6%, especially in 3T (Disadvantaged, Remote, and Outermost) areas such as Bengkulu and East Nusa Tenggara (NTT). One of the main obstacles is the limited tools to detect stunting risk and the lack of maternal role in prevention. For this reason, the One House One Stunting Risk Detection Measuring Tool (ALKURTING) intervention was developed. The study used a quasi-experimental design involving 120 clown mothers from Kupang Regency, NTT, and Kepahyang Regency, Bengkulu. Samples were selected using purposive sampling. Inclusion criteria include mothers aged 20-40 years, who live in the local area and can read and write, and children who do not have comorbidities. The instruments used were questionnaires, feasibility test forms, and forms for filling out anthropometric survey results. Data analysis through feasibility tests and intervention effectiveness tests. The feasibility test showed that ALKURTING was very good, with a percentage of media feasibility of 86.8% and material feasibility of 83.3%, meaning that almost all mothers recommended ALKURTING users. The 1 house 1 ALKURTING intervention effectively increased the score of knowledge, attitudes, and skills of clown mothers in Kepahyang and Kupang Regency (p-value<0.05). ALKURTING is a tool suitable for detecting stunting risk in 3T areas. The One House One ALKURTING intervention is effective in improving maternal behavior in detecting stunting risk. It is necessary to expand the intervention to other 3T areas in Indonesia.